PEMBERITAHUAN KONSULER SEBAGAI BENTUK PELAKSANAAN HAK ASASI MANUSIA DITINJAU DARI KASUS AVENA - Jennifer Jennifer; Arif Arif; Sutiarnoto Sutiarnoto (Journal of USU International Law, 2013)
AbstractSince 17 Century, relation between States has been developing until today. In the process of the relationship, national from every country is one of the concern. National’s right is protected under international law especially in Vienna Convention 1961 concerning Diplomatic Relation and Vienna Convention 1963 concerning Consular Relation. Consular Notification is one of the rights that are protected for people who live in other countries. No one needs national protection more than someone who is accused at another country. Nowadays, many countries tend to violate that rule although they have ratified it. Many cases happened and submitted under the International Court of Justice can be the proves for it. Case Concerning Avena and other Mexican Nationals (Mexico v. United State of America) is one of the case that shows how important the rule of consular notification is.Keyword: Consular Relation, Consular Notification, National